Diversity of Culinary Ecolexicon of Main Cuisine in Malay Communities on the East Coast of North Sumatra - Dwi Widayati (JURNAL ARBITRER, 2019)
This paper aims to describe the diversity of the main culinary eco-lexicon in Malay society. Data were collected through interviews with informants who were very familiar with the traditional culinary eco-lexicon. An in-depth discussion with content analysis is carried out on each culinary eco-lexicon, especially in the effort of meaning and description. The analysis of the diversity of culinary eco-lexicon is done by using ecolinguistic theory. From the results of the analysis it was concluded that there is a diversity of culinary eco-lexicons which refer to certain types of culinary, for example for culinary weaving, four variations of the eco-lexicon, namely anyang buas-buas (Langkat Malay, and Asahan Malay), anyang sibuas-savas leaves (Serdang Malay), anyang sibuih-buih (Batubara Malay), and labar buas-buas (Panai Malay). It indicates that the eco-lexicon diversity of culinary names and types of herbs reflects the understanding of the speaker toward their environment. The more lexicons use to reflect the environment indicates the richness of the environment itself.